IUMPA: The presentation of the aim of using the intrauterine drug delivery system for the hormone preoperative treatment of endometrial cancer and the hormone treatment of abnormal uterine bleeding - Kowalski, Andrzej J.; Zdziennicki, Andrzej; Welfel, Jakub; Surkont, Grzegorz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2007)
Introduction: In the review the intrauterine drug delivery system releasing medroxyprogesterone acetate is shown. This system has been used for preoperative treatment of endometrial cancer and hormone treatment of abnormal uterine bleeding. The system is named IUMPA (IntraUterine MedroxiProgesterone Acetate). Aim: IUMPA-1 has been prepared for preoperative treatment of endometrial cancer, IUMPA-2 for cases of abnormal bleeding from the uterine cavity. Methods: Medroxyprogesterone acetate was used in both systems. Materials: IUMPA-1 – patients with endometrial cancer, IUMPA-2 – patients with abnormal bleeding. Conclusions: IUMPA-1 was found to be an effective system for preoperative treatment of endometrial cancer. IUMPA-2 only in cases with relative hyperoestrogenism, in which increased administration of progestogen was needed, was successful. In other cases success was not noted. Recapitulation: The Drug Delivery System IUMPA can be used as an alternative or supplementary instrument in selected gynaecological cases.